2008
DOI: 10.1063/1.2830696
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and efficiency of GaNP light emitting diodes

Abstract: GaNP / GaP is promising for yellow-amber-red light emitting diodes ͑LEDs͒. In this study, pressure and temperature dependent electroluminescence and photocurrent measurements on bulk GaP / GaN 0.006 P 0.994 / GaP LED structures are presented. Below ϳ110 K, emission is observed from several localized nitrogen states. At room temperature, the band-edge energy increases weakly with pressure at a rate of +1.6 meV/ kbar, substantially lower than the ⌫ band gap of GaP ͑+9.5 meV/ kbar͒. Thus, despite the multiplicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
2
18
1
Order By: Relevance
“…E N was found from interpolation of the isolated nitrogen level in GaAs and GaP and has been assumed to have a negligible pressure dependence. 16 It is clearly seen in Fig. 1 that the BAC model gives good agreement with the experimental data for which C MN = 1.9 eV.…”
Section: Materials Sciences Center and Department Of Physicssupporting
confidence: 68%
See 2 more Smart Citations
“…E N was found from interpolation of the isolated nitrogen level in GaAs and GaP and has been assumed to have a negligible pressure dependence. 16 It is clearly seen in Fig. 1 that the BAC model gives good agreement with the experimental data for which C MN = 1.9 eV.…”
Section: Materials Sciences Center and Department Of Physicssupporting
confidence: 68%
“…Hence we conclude that the leakage level has a slightly smaller pressure dependence than the CB quasi-Fermi level. This suggests that leakage into the X minima of the indirect barriers ͑as previously observed in shorter wavelength GaNP light emitting diodes 16 ͒ is not significant here, as the leakage level would then have a negative pressure coefficient. In summary, we have found that the BAC model can well describe the band gap of GaNAsP/GaP as a function of pressure.…”
Section: Materials Sciences Center and Department Of Physicsmentioning
confidence: 75%
See 1 more Smart Citation
“…The C CB is found above the Xxy CB for all composition range, in agreement with the results of Prieto et al 26 for the case of GaAs strained layer on GaP(001) which is observed slightly indirect near the X-point. The N-level is insensitive to strain as in reported previous works 27,28 and lies below the CB of strained GaAsP whatever the content. Fig.…”
supporting
confidence: 52%
“…However, recent development in light emitting diodes (LEDs) 1 and water splitting, 2 taking advantage of its transparency and band energy levels, raised interests in materials based on the GaP platform. The small difference in the lattice constants between GaP and Si (5.451 Å and 5.431 Å , respectively) also provides a III-V-on-Si integration opportunity.…”
mentioning
confidence: 99%